Characteristic findings by phototrichogram in southern Chinese women with Female pattern hair loss. Issue 4 (7th January 2019) - Mai, Weihua; Sun, Yixian; Liu, Xingwei; Lin, Daojian; Lu, Dongqing
Abstract: Objectives: To investigate the characteristics of hairs in Female pattern hair loss (FPHL) patients and healthy females in Southern China. Materials and methods: Three fundamental hair parameters in different scalp areas of 90 Southern Chinese FPHL patients and 83 healthy controls were analyzed by phototrichogram. Results: Female pattern hair loss patients showed reduced hair density, hair diameter, and terminal/vellus hair ratio. The reduction correlated with the severity of Ludwig staging. Midscalp was the most affected area in FPHL, but occipital and temporal sites were also involved. In normal women, the highest hair density was observed in midscalp, followed by occipital and temporal areas. Peak hair density at midscalp sites was reached at 20s group, then declined with age. Maximum hair diameter at midscalp and occipital sites occurred in 40s group. Terminal/vellus hair ratio tended to increase with age and peak on 50‐60s group. Conclusion: Reduced hair density and hair diameter, and miniaturization of hair follicles are the characteristics of FPHL in Southern Chinese women. Occipital and temporal sites are also affected in FPHL. Age‐associated changes might have an influence on the hair condition. The values of hair parameters obtained in this study will help to establish reference data for better evaluation of hair disorders.